PERANAN BANK DALAM PENDANAAN KREDIT USAHA MIKRO, KECIL, DAN , MENENGAH - Aulia Rahman Putra Ramadhan (2022)
This article aimed to identify and analyze of banks in financing small and medium business .. The samples were 5 business- men categorized as small and medium business and 65 responded. Analysis tool used was descriptive approach. The result of this research was the role of banks in the development of small and medium business . This was because the role of non-bank credit and financial institutions in the financing of small and medium business was still relatively low. The contribution of banks, particularly in supporting finance was when small and medium business entered business development. When obtaining a bank loan, small and medium business categorized as potential, feasible, and bankable, did not usually meet difficul- ties. On the other hand, the potential small and medium business categorized feasible but not bankable and categorized not feasible but bankable facilitated access to bank financing requiring a variety of support programs from government and also Bank Indonesia. Further, for potential small and medium business but not feasible and not bankable the financial support was not through banks but through the revolving fund programs and social assistance funds.